CULTURAL HERITAGE AND THE REGULATION OF RELIGIOUS FREEDOM: THE CASE OF POLAND AND CZECH REPUBLIC - Szymaniec, Piotr (2018)
AbstractThe paper poses the question of the extent to which the difference of religious structure and religiosity between Poland and the Czech Republic has an impact on regulations on religious freedom. Based on historical research the author claims that, despite this difference, after the collapse of the Soviet system both Poland and the Czech Republic decided to reintroduce the same “co-operative” model of the relations between state and churches and religious associations, which already had been implemented in the interwar period (1918–1939) and should be considered as a part of Prussian and Austro-Hungarian legal legacy. Reintroducing this model could be perceived as the return to the heritage of legal history and legal culture. It is emphasized, however, that the religious nature of a society influences the implementation of legal provisions, and on that ground confessional elements in Polish legal system are more noticeable than in the Czech Republic.Key words: Poland, Czech Republic, church–state relations, religious freedom, religious associations, national identity.